KEEFEKTIFAN MODEL MIND MAPPING BERBANTU MEDIA AUDIOVISUAL PADA MATA PELAJARAN IPA TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI JRAGUNG 3 DEMAK - Randy Dwi Saputra; Ernawati Saptaningrum; Ikha Listyarini (Universitas Negeri Medan, 2019)
Abstract: The Effectiveness of Mind Mapping Models Assisted by Audivisual Media in Natural Sciences Subjects on Learning Outcomes of Grade IV Students of SDN Jragung 3 Demak. This study aims to determine whether the mind mapping learning model assisted by audiovisual media is effective against the learning outcomes of Natural Sciences subject class IV SD Negeri Jragung 3 Demak.This type of research is quantitative with pre-experimental design research methods with one-group pretest-posttest design. Data in this study were obtained through interviews, documentation, and tests.The results of the analysis of the initial normality test data (pretest) L0 0.1216 <Ltable 0.173 then H0 is accepted and the data comes from the normal distribution. In addition, the results of the analysis of the final normality test data (posttest) L0 0.1081 <Ltabel 0.173 then H0 is accepted and the data comes from the normal distribution. Furthermore, the results of t test analysis obtained tcount 5.374> ttable 1.708 then H0 is rejected and Ha is accepted. On student learning outcomes achieve classical learning completeness with a pretest percentage of 30.77% and 65.38% posttest. The conclusion is that the mind mapping learning model assisted with audiovisual media is effective towards the learning outcomes of Natural Sciences subject class IV SD Negeri Jragung 3 Demak.Keywords:Mind Mapping, Audiovisual Media, Learning OutcomesAbstrak: Keefektifan Model Mind Mapping Berbantu Media Audivisual Pada Mata Pelajaran IPA Terhadap Hasil Belajar Siswa Kelas IV SDN Jragung 3 Demak. Penelitian ini bertujuan untuk mengetahui apakah model pembelajaran mind mapping berbantu media audiovisual efektif terhadap hasil belajar mata pelajaran IPA kelas IV SD Negeri Jragung 3 Demak. Jenis penelitian ini adalah kuantitatif dengan metode penelitian pre-experimental design dengan desain one-group pretest-posttest. Data dalam penelitian ini diperoleh melalui wawancara, dokumentasi, dan tes. Hasil analisis data uji normalitas awal (pretest) L0 0,1216 < Ltabel 0,173 maka H0 diterima dan data berasal dari distribusi normal. Selain itu hasil analisis data uji normalitas akhir (posttest) L0 0,1081 < Ltabel 0,173 maka H0 diterima dan data berasal dari distribusi normal. Selanjutnya hasil analisis uji t diperoleh thitung 5,374 > ttabel 1,708 maka H0 ditolak dan Ha diterima. Pada hasil belajar siswa mencapai ketuntasan belajar secara klasikal dengan persentase pretest 30,77% dan posttest 65,38%. Kesimpulannya bahwa model pembelajaran mind mapping berbantu media audiovisual efektif terhadap hasil belajar mata pelajaran IPA kelas IV SD Negeri Jragung 3 Demak. Kata Kunci :Mind Mapping, Media Audiovisual, Hasil Belajar